VARIASI BAHASA DALAM KOLOM MELA KOMENTAR SURAT KABAR RAKYAT BENGKULU - Hotlan Siboro; Dian Eka Chandra; Ngudining Rahayu (Universitas Bengkulu, 2018)
The purpose of this study is to describe the variation of spoken language in the column Mela Bengkulu People's newspaper commentary and language variations in the column Mela Bengkulu People's newspaper comments in terms of formality. This research uses descriptive research design and using documentation technique as data collection tool. For data analysis, the following steps are used: (1) read carefully, (2) code every data obtained, (3) tabulate data used to describe language usage, (4) analyze data of spoken language in terms of level (5) classify the results of data analysis, (6) synthesize the results of classification, (7) conclude. From the result of the research, it is found that the variation of language in Mela Comments column used standard oral language and non standard oral language. Language variations seen in terms of formality are used diverse casual and familiar variety. The marker of standard oral spoken language is seen in the use of Indonesian vocabulary and diction and no regional language elements. Markers of oral spoken language use are not seen in non-standard word usage, regional/foreign language usage, slang usage and presence of expression statements. Markers of casual usage are seen in the use of regional/foreign languages, the use of non-standard words, the use of slang and expressions. The use of familiar varieties is seen in the use of the word hello, the use of regional/foreign languages and typical terms. Conclusion; Language variations in the October 26 to 24 November 2016 edition of Mela Comments column of 26 topics with 265 speeches, can be summarized by 38 speeches using standard oral language and 227 using non-standard spoken language. Language variations are viewed in terms of its formality using a variety of casual and diverse. Keywords: language variation, mela komentar column, Rakyat Bengkulu newspaper